Remediation of the alkalinity of steel mill powders by sequential washing with organic acids - Delvasto, Pedro (2011)
Residual steelmaking powders, coming from a Venezuelan steel mill, were characterized physicochemically, detecting that they had high contents of heavy metals such as Fe, Zn and Pb and a high pH of contact, greater than 12 units, which makes it a waste dangerous due to its tendency to generate leachates with high alkalinity. Due to these results, a remediation process of the residue was proposed through sequential washes with dilute solutions of (CH2) 2COH (COOH) 3 (citric acid), (COOH) 2 (oxalic acid), CH3COOH (acetic acid) and H2SO4 ( sulfuric acid). It was obtained that the CH3COOH solution generated the greatest attenuation of the alkalinity of the powders, reaching acidity until a pH of around 4 units.